2009
DOI: 10.1177/1557988309335822
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Women’s Perceptions About Their Role in Supporting Partners’ and Sons’ Reproductive Health Care

Abstract: Women serve as important health information sources for young men. No previous study has explored women's perceptions about this role related to young men's sexual and reproductive health (SRH) care. Twenty African American women recruited from two clinics participated in three focus groups to explore perceptions to engage young men in SRH care. Themes were identified that may facilitate and/or hinder women to engage young men in SRH care: 1) communication/actions to provide support; 2) challenges in providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
2
20
0
2
Order By: Relevance
“…Participants were somewhat unaware of the consequences of HPV for men (44% correctly knew that HPV can cause serious health problems for men) and opportunities for vaccination for men (40% incorrectly thought the HPV vaccine is only for females). Women may act as important sources of health information for male partners, family, or friends and could be a channel for increasing knowledge around HPV and the HPV vaccine for men (Norcross, Ramirez, & Palinkas, 1996;Marcell, Howard, Plowden, & Watson, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Participants were somewhat unaware of the consequences of HPV for men (44% correctly knew that HPV can cause serious health problems for men) and opportunities for vaccination for men (40% incorrectly thought the HPV vaccine is only for females). Women may act as important sources of health information for male partners, family, or friends and could be a channel for increasing knowledge around HPV and the HPV vaccine for men (Norcross, Ramirez, & Palinkas, 1996;Marcell, Howard, Plowden, & Watson, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Marcell, Howard, Plowden, and Watson (2009), in their focus group research, found that women are enthusiastic about the idea of sharing health information, making clinic appointments, attending appoint ments, and making joint appointments with young male relatives concerning sexual and reproductive health issues. Marcell et al suggest that, given this level of willingness, as well as women's typically greater experience with the health care system, they would make ideal health promotion agents for men.…”
Section: Discussion and Key Findingsmentioning
confidence: 99%
“…These barriers include fear; stigma; shame; denial; lack of social support; lack of confidential services; lack of health insurance options especially as they get older; and not knowing where to go for care. [141][142][143][144][145][146] Given the asymptomatic nature of many STIs, including HIV infection, strategies are needed to raise young men's awareness about sexual/reproductive health services, STI and HIV testing options, and related resources. Promoting sexual/reproductive health for young men can lead to sexual responsibility, healthy intimate relationships, and responsible fatherhood.…”
Section: Male Adolescents' Sexual/ Reproductive Health Care Usementioning
confidence: 99%